Assessment of diastolic dysfunction in patients with acute coronary syndrome and preserved systolic function: comparison between Doppler transthoracic echocardiography and velocity-encoded cardiac magnetic resonance - Mohd Shah, Azarisman Shah; Mitra, Shirazi; Bradley, Julie Andrew; Teo, Karen S.L; Worthley, Matthew Ian; Worthley, Stephen Grant (Acta Cardiologica, 2016)
Objectives: Transthoracic echocardiography (TTE) remains the mainstay diagnostic imaging tool for the assessment of diastolic dysfunction.However, velocity-encoded phase-contrast imaging permits evaluation with cardiac magnetic resonance (CMR) with excellent capabilities to assess blood flow and myocardial tissue motion. We evaluated the feasibility of measuring mitral blood flow, mitral annular velocity and pulmonary vein flow in assessing diastolic dysfunction in acute coronary syndrome (ACS) patients. Methods: Revascularized acute myocardial infarction patients with normal left ventricular (LV) systolic function on TTE were assessed by 1.5T CMR.Following acquisition of regular short-axis cine volumetry and 2-, 3- and 4-chamber views, we performed single-slice velocity-encoded phase-contrast imaging in short-axis plane at the level of the mitral leaflet tips and in a plane perpendicular to a pulmonary vein. Early, late diastolic mitral inflow velocities, peak systolic, diastolic pulmonary vein velocities and myocardial annular velocities were determined. These were then compared to comparable TTE parameters. Results: Fourty-six patients were analyzed. Mean LVEF was 61.1±8.9%. Peak E and A velocities underestimated by CMR, E/A ratio showed a significant correlation with TTE, R2 0.51. Peak S and D velocities also underestimated, S/D ratio significantly correlated with TTE, R2 0.58. Paradoxically, E’ is overestimated by CMR, with lower E/E’ ratio but still significantly correlated with TTE, R2 0.55. Bland-Altman analysis demonstrated excellent agreement with excellent reproducibility. Conclusion: CMR evaluation of diastolic dysfunction post-ACS has significant correlation with TTE. Although velocity-encoded phase-contrast imaging underestimates inflow velocities, and overestimates the mitral annular velocity, velocity ratios are consistently correlated with Doppler echocardiography.